Targeted preventive vaccination campaigns to reduce Ebola outbreaks: An individual-based modeling study. Issue 3 (16th January 2023) - Bisanzio, Donal; Davis, Ashley E.; Talbird, Sandra E.; Van Effelterre, Thierry; Metz, Laurent; Gaudig, Maren; Mathieu, Valérie Oriol; Brogan, Anita J.
Highlights: Existing Ebola interventions are implemented after an outbreak is declared. Preventive vaccination may provide a complementary option to help protect against unpredictable outbreaks. Our novel individual-based Ebola transmission model accounted for important disease transmission factors, such as human movement and contact heterogeneity. Targeted preventive vaccination reduced Ebola cases, hospitalizations, and deaths. Preventive vaccination flattened epidemic curves, protecting healthcare systems and providing more time to implement additional interventions. Abstract: Introduction: Nonpharmaceutical interventions (NPI) and ring vaccination (i.e., vaccination that primarily targets contacts and contacts of contacts of Ebola cases) are currently used to reduce the spread of Ebola during outbreaks. Because these measures are typically initiated after an outbreak is declared, they are limited by real-time implementation challenges. Preventive vaccination may provide a complementary option to help protect communities against unpredictable outbreaks. This study aimed to assess the impact of preventive vaccination strategies when implemented in conjunction with NPI and ring vaccination. Methods: A spatial-explicit, individual-based model (IBM) that accounts for heterogeneity of human contact, human movement, and timing of interventions was built to represent Ebola transmission in the Democratic Republic of the Congo. Simulated preventive vaccination strategies targeted healthcare workers (HCW), frontline workers (FW), and the general population (GP) with varying levels of coverage (lower coverage: 30% of HCW/FW, 5% of GP; higher coverage: 60% of HCW/FW, 10% of GP) and efficacy (lower efficacy: 60%; higher efficacy: 90%). Results: The IBM estimated that the addition of preventive vaccination for HCW reduced cases, hospitalizations, and deaths by ∼11 % to ∼25 % compared with NPI + ring vaccination alone. Including HCW and FW in the preventive vaccination campaign yielded ∼14 % to ∼38 % improvements in epidemic outcomes. Further including the GP yielded the greatest improvements, with ∼21 % to ∼52 % reductions in epidemic outcomes compared with NPI + ring vaccination alone. In a scenario without ring vaccination, preventive vaccination reduced cases, hospitalizations, and deaths by ∼28 % to ∼59 % compared with NPI alone. In all scenarios, preventive vaccination reduced Ebola transmission particularly during the initial phases of the epidemic, resulting in flatter epidemic curves. Conclusions: The IBM showed that preventive vaccination may reduce Ebola cases, hospitalizations, and deaths, thus safeguarding the healthcare system and providing more time to implement additional interventions during an outbreak.